Shedding Light : Understanding Energy Efficiency and Electricity Reliability - Carranza, Eliana; Meeks, Robyn (World Bank, Washington, DC, 2016)
Overloaded electrical systems are a major source of unreliable power (outages) in developing countries. Using a randomized saturation design, we estimate the impact of energy efficient lightbulbs on household electricity consumption and local electricity reliability in the Kyrgyz Republic. Receiving compact fluorescent lamps (CFLs) significantly reduced household electricity consumption. Estimates not controlling for spillovers in take-up underestimate the impacts of the CFLs, as control households near the treated are likely to take-up CFLs themselves. Greater saturation of CFLs within a transformer leads to aggregate reliability impacts of two fewer days per month without electricity due to unplanned outages relative to pure controls. Increased electricity reliability permits households to consume more electricity services, suggesting that CFL treatment results in technological externalities. The spillovers in take-up and technological externalities may provide an additional explanation for the gap between empirical and engineering estimates of the impacts of energy efficient technologies.